(untitled) (Raparin Journal of Humanities (RJH), 2024)
This study is entitled “Compound Words of Central Kurdish from the Perspective of Configuration Theory”. to analyzes compound words from the perspective of Configuration theory. The scope is within the framework of Cognitive Morphology based on Zaki Hamawand (2011). The importance of this research is the originality as the first work in Kurdish language on the mentioned field above. The concept and meaning of compound words are changed, according to people’s view and experiences. They fall into different domains, which is the problem. The aim of the study is to find a solution from the perspective of configuration theory for it, and identify the domain and facet, that include Central Kurdish compound nouns and compound adjectives. The focus is only on compound nouns and adjectives among compound words for analysis process. In addition to the researcher’s interest and being native in the targeted language, the used materials are taken from library data that are used as sources in the study. The paper consists of an introduction, two sections, conclusions, and the list of references. As a result, the domains and facets that contain Middle Kurdish compound nouns and compound adjectives are identified, which are explained by distinguishing two kinds: first, Compound words in Inter-class words. Second, Compound words in Intra-class words.